2022
DOI: 10.3389/fphar.2022.854994
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Release Contributes to Intestinal Ischemia/Reperfusion Injury

Abstract: Mitochondria release many damage-associated molecular patterns (DAMPs) when cells are damaged or stressed, with mitochondrial DNA (mtDNA) being. MtDNA activates innate immune responses and induces inflammation through the TLR-9, NLRP3 inflammasome, and cGAS-STING signaling pathways. Released inflammatory factors cause damage to intestinal barrier function. Many bacteria and endotoxins migrate to the circulatory system and lymphatic system, leading to systemic inflammatory response syndrome (SIRS) and even dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 194 publications
(209 reference statements)
0
18
0
Order By: Relevance
“…MtDNA activates the innate immune responses and mediates inflammation through the TLR-9, NLRP3 inflammasome, and cGAS-STING signaling pathways. 91 In addition, the regulation of mitochondria in innate immunity is affected by intermediate products of the metabolic pathway. Itaconate (ITA) is a Krebs cycle metabolite with anti-inflammatory activity.…”
Section: Treatment Of Sepsis By Regulating Mitochondrial Functionmentioning
confidence: 99%
“…MtDNA activates the innate immune responses and mediates inflammation through the TLR-9, NLRP3 inflammasome, and cGAS-STING signaling pathways. 91 In addition, the regulation of mitochondria in innate immunity is affected by intermediate products of the metabolic pathway. Itaconate (ITA) is a Krebs cycle metabolite with anti-inflammatory activity.…”
Section: Treatment Of Sepsis By Regulating Mitochondrial Functionmentioning
confidence: 99%
“…Mechanically, in the TLR9 signaling pathway, mtDNA binds to the TLR9 of neutrophils to stimulate neutrophils to release measuring matrix metalloproteinase (MMP)-8 and MMP-9 and produce TNF-α, IL-1, IL-6, and other proinflammatory factors. Furthermore, in the NLRP3 signaling pathway, mtDNA is released into the cytoplasm after mitochondrial injury, then induces the activation of the NLRP3 inflammasome, and contributes to the secretion of IL-1ÎČ and IL-18 ( Liao et al., 2022 ).…”
Section: Novel Role Of Metabolism-associated Molecular Patterns In Se...mentioning
confidence: 99%
“…Intestinal I/R involves a complex mechanism. In the event of I/R, intestinal immune barrier dysfunction will lead to cytokine release, intestinal inflammatory injury and bacterial invasion and migration [ 6 ], resulting in serious body damage. Many studies have demonstrated successful application of BMSCs in reducing intestinal mucosal I/R damage in animal models [ 7 , 8 ], which proposing a new strategy for the management of intestinal I/R impairments.…”
Section: Introductionmentioning
confidence: 99%